2020
DOI: 10.1101/2020.05.05.078766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbe-dependent heterosis in maize

Abstract: Hybrids account for nearly all commercially planted varieties of maize and many other crop plants, because crosses between inbred lines of these species produce F1 offspring that greatly outperform their parents. The mechanisms underlying this phenomenon, called heterosis or hybrid vigor, are not well understood despite over a century of intensive research (Birchler et al. 2003). The leading hypotheses-which focus on quantitative genetic mechanisms (dominance, overdominance, and epistasis) and molecular mechan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…To increase the level of sustainability, various agroecological management strategies of agricultural production systems have been reviewed, including the use of microorganisms in the process of plant domestication, genetic improvement, and the production of improved varieties. According to the references presented in the scientific literature, to increase agricultural production and the sustainability of production systems, future research should develop breeding methods that optimize symbiosis in crops [9], since the interactions with soil microorganisms could be important for the expression of heterosis in some species [20], proposing an alternative framework to produce new phenotypes by modifying genomic information and the microbiota associated with plants [3]; efficient interaction with certain beneficial microorganisms is expected to be an additional factor in plant production. These new agricultural practices can include the reproduction of the microbiome, the transplantation and engineering of specific microbiomes [30] and their transfer through seeds [3,43] or in vitro culture [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the level of sustainability, various agroecological management strategies of agricultural production systems have been reviewed, including the use of microorganisms in the process of plant domestication, genetic improvement, and the production of improved varieties. According to the references presented in the scientific literature, to increase agricultural production and the sustainability of production systems, future research should develop breeding methods that optimize symbiosis in crops [9], since the interactions with soil microorganisms could be important for the expression of heterosis in some species [20], proposing an alternative framework to produce new phenotypes by modifying genomic information and the microbiota associated with plants [3]; efficient interaction with certain beneficial microorganisms is expected to be an additional factor in plant production. These new agricultural practices can include the reproduction of the microbiome, the transplantation and engineering of specific microbiomes [30] and their transfer through seeds [3,43] or in vitro culture [46].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that advances in the development of maize hybrids have had a significant impact on the microbial communities of the rhizosphere and on the assembly of their interaction networks. Wagner et al [20] found that interactions with soil microorganisms are important for the expression of heterosis in corn and Zambonin et al [21], found no significant interaction between corn hybrids and inoculation with Azospirillum sp. for the variables studied including grain yield, and the specificity between maize hybrids and inoculation was not verified.…”
Section: Crop Domestication and Microbial Diversitymentioning
confidence: 99%
“…The significance of the variance components show in this case that the effect of treatments was similar to or greater than the effect of the corn hybrids per se, which suggests that the response in grain yield in the corn cultivars may be balanced with nitrogen fertilization and inoculation with Azospirillum sp. ; this aspect has been studied by Wagner et al (2020) who demostrated that interactions with soil microorganisms are important for the expression of heterosis in corn.…”
Section: Discussionmentioning
confidence: 99%
“…Correa-Galeote et al (2016) suggested that the genotype of Andean starchy maize could be the main factor in controlling bacterial diversity in its rhizosphere, either in monoculture or in association with other plants. The results of Wagner et al (2020) show that interactions with soil microorganisms are important for the expression of heterosis in corn. Recently, SCAR-type molecular markers have been developed for the identification of A. brasilense (Coniglio et al 2020).…”
Section: Introductionmentioning
confidence: 97%
“…A commonly observed form of background effect among individuals carrying the same mutation is different degrees of response to that mutation (or ‘variable expressivity’) (4). Variable expressivity can arise due to a myriad of reasons, including genetic interactions (or epistasis) between a mutation and segregating loci (1), dominance (1), stochastic noise (5), the microbiome (6), and the environment (1).…”
Section: Introductionmentioning
confidence: 99%